Pengaruh Pendidikan Agama Islam Terhadap Akhlak (Perilaku Jujur) - Besse Tanri Akko (Institut Agama Islam Negeri Palopo, 2018)
This study aims to determine the effect of Islamic Education Against Morals (Honest Behavior) of Class X Students in SMA 3 Palopo. This study uses a causal ex-post facto research design with a population of 277 class X students with sampling using a probability sampling technique with a simple random sampling technique established by 73 students. Data collection techniques in this study used observation, documentation and questionnaire techniques. The results of data processing obtained an average score of Islamic education, which is 86.40 with a standard deviation of 7.684 from the ideal score of 100. Similarly, the average score of honest behavior is 88.77 with a standard deviation of 5.760 of the ideal score of 100. The results his research shows that Islamic religious education has a significant influence on the honest behavior of class X students in SMA 3 Palopo with a percentage of 17.2%, while the rest is influenced by other factors. The implication of this research is that if Islamic religious education is taught well it will have a big influence on the formation of the morality of students, the especially honest character which students will actualize in their daily lives both for themselves and for others.